Embedded extraterritoriality: US judicial litigation and the global banking surveillance of digital money flows - Mallard, Grégoire (Research Handbooks in International Law series, 2021)
Following the 9/11 terrorist attacks, North American/European governments have emphasized the importance of money and financial datamining in combating terrorism and nuclear proliferation. The 'digitalization' of money flows is part of this campaign. Adopting new software packages for financial data management is supposed to help global banks and states counter money laundering and terrorism financing. This chapter shows how such technologies have embedded the practices of compliance officers in global banks not only in a new transnational set of rules but also in US domestic legal requirements. Deferred prosecution agreements signed by many European headquartered global banks and US judicial authorities in the 2010s remained remarkably similar. This chapter also surveys how banks reacted to the obligations to install US government-approved monitoring software developed overwhelmingly by US-based vendors. It examines the question of 'extra-territoriality' from the socio-technical viewpoint rather than by a purely textual legal analysis.